Seasonally contrasting responses of evapotranspiration to warming and elevated CO2 in a semiarid grassland. Issue 7 (17th July 2017) - Sorokin, Y.; Zelikova, T. J.; Blumenthal, D.; Williams, D. G.; Pendall, E.
Abstract: Global climate change is expected to alter seasonal patterns and rates of evapotranspiration in dry regions. Although climate change will involve elevated CO2 and increased temperatures, independently, these factors may have different impacts on actual evapotranspiration (AET) due to their opposing effects on transpiration. We used canopy gas exchange chambers to quantify AET in a semiarid grassland experimentally altered by elevated CO2 and warming over 3 years with contrasting ambient precipitation. Seasonal and interannual variations in AET due to background climate variability were larger than the effects of climate manipulation treatments. However, in a year with average precipitation, cumulative growing season AET was suppressed by warming by 23%. Across years, warming increased AET early in the growing season and suppressed it later in the growing season. By contrast, elevated CO2 suppressed AET early in the growing season and enhanced it later, but only in years with average or above‐average precipitation. Vegetation greenness (a proxy for photosynthetically active leaf area) was consistently the strongest predictor of AET, whereas soil moisture and vapor pressure deficit were secondary drivers. Our research demonstrates that effects of increased atmospheric CO2 and temperature on AET will be mediated by plant phenological development and seasonal climatic conditions.